2019
DOI: 10.1039/c8dt03696a
|View full text |Cite
|
Sign up to set email alerts
|

Exploring transition metal fluoride chelates – synthesis, properties and prospects towards potential PET probes

Abstract: A series of 1st row transition metal trifluoride complexes with neutral N3-donor ligands is described; radiolabelling of [FeF3(BnMe2-tacn); in aqueous MeCN is achieved by 18F/19F isotopic exchange and its stability in PBS and serum established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 62 publications
0
8
1
Order By: Relevance
“…Although high molar activity is only necessary to image low-density targets, such as neuroreceptors, there have been several new drug candidates that do not stringently require high molar activity during the initial assessments of their pharmacological properties. In addition, 18 F/ 19 F isotopic exchange has proven to be useful in various applications, as shown in Figure a, and can be a valuable alternative to yield 18 F-labeled PET radiopharmaceuticals or radiotracers, especially when considering that other approaches to introduce 18 F are ineffective. Moreover, this approach relieves the synthetic burden of separate preparation of labeling precursors and avoids the extra screening process required for judicious radiolabeling methods.…”
mentioning
confidence: 99%
“…Although high molar activity is only necessary to image low-density targets, such as neuroreceptors, there have been several new drug candidates that do not stringently require high molar activity during the initial assessments of their pharmacological properties. In addition, 18 F/ 19 F isotopic exchange has proven to be useful in various applications, as shown in Figure a, and can be a valuable alternative to yield 18 F-labeled PET radiopharmaceuticals or radiotracers, especially when considering that other approaches to introduce 18 F are ineffective. Moreover, this approach relieves the synthetic burden of separate preparation of labeling precursors and avoids the extra screening process required for judicious radiolabeling methods.…”
mentioning
confidence: 99%
“…Blower et al showed similar results (Scheme b) that [FeF 3 (BnMe 2 -tacn)] ( 128 ) can be obtained by coordinating tacn derivatives with FeF 3 , which not only exhibited good stability but also requires only 24 nM of precursor amount to achieve the corresponding radiofluorination (Table ).…”
Section: F/19f Isotope Exchange On Metal Atomsmentioning
confidence: 99%
“…Aqueous 18 F-labeling via FeÀ 18 F bond formation More recently, Reid's group continued to evaluate possible applications of d 3 -transition metal (Cr(III), Mn(III), Fe(III), and Co(III)) trifluoro compounds in the development of PET tracers (Scheme 26). [107] They reported the first example of direct 18 Ffluorination of transition metal Fe through the formation of three fluorine substitutions FeÀ 18 F bonds in one step via isotope exchange by using the same ligand as that used for GaF 3 to form a chelate-like complex. The reaction was conducted at 80 °C using 2.4 nmol of the precursor in CH 3 CN/H 2 O (v/v = 75/ 25), and ~13 % RCY was obtained.…”
Section: Aqueous 18 F-labeling Via Alà 18 F Bond Formationmentioning
confidence: 99%